Strengthening Religious Moderation through Learning Media Innovation in High Schools - Siti Rukayah; Meilisa Sajdah; Ratna Himawati (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
This study aims to strengthen the values of religious moderation in senior high schools through the development and implementation of innovative learning media. Utilizing a Research and Development (R&D) approach adapted from the Borg and Gall model, the research was conducted through several stages including needs analysis, product development, expert validation, limited testing, and broader implementation. The learning media developed consisted of digital modules, interactive videos, and infographics that incorporated key values of religious moderation such as tolerance, anti-violence, and appreciation of diversity. The findings indicate that innovative media significantly enhance students' cognitive understanding and affective commitment to religious moderation. Students not only improved their conceptual grasp of pluralism but also showed greater empathy and inclusiveness in social interaction. This study concludes that the integration of digital-based, contextually relevant, and value-oriented media is a powerful tool in shaping moderate religious attitudes among high school students.